2022
DOI: 10.3390/met12071108
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly Recovery of Lithium from Lithium–Sulfur Batteries

Abstract: In the context of the rising demand for electric storage systems, lithium–sulfur batteries provide an attractive solution for low-weight and high-energy battery systems. Considering circular economy for new technologies, it is necessary to assure the raw material requirements for future generations. Therefore, metallurgical recycling processes are required. Since lithium is the central and most valuable element used in lithium–sulfur batteries, this study presents an environmentally friendly and safe process f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Park et al [33] investigated the thermal treatment of pure NMC 811 and graphite mixtures under CO 2 and gained higher Li 2 CO 3 recovery rates by water leaching compared to inert N 2 treatment. Schwich et al [34] reported a leaching efficiency of 60% for thermally treated NMC black mass under a CO 2 atmosphere, but without focus on the behavior or influence of CO 2 during the thermal treatment compared to other flow-gas compositions. For a better understanding of the process and in order to develop further optimization options for thermal treatment, the present study investigates the influence of different flow-gas compositions on both the off-gas and the black mass achieved, as well as the effects on the ESLR process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al [33] investigated the thermal treatment of pure NMC 811 and graphite mixtures under CO 2 and gained higher Li 2 CO 3 recovery rates by water leaching compared to inert N 2 treatment. Schwich et al [34] reported a leaching efficiency of 60% for thermally treated NMC black mass under a CO 2 atmosphere, but without focus on the behavior or influence of CO 2 during the thermal treatment compared to other flow-gas compositions. For a better understanding of the process and in order to develop further optimization options for thermal treatment, the present study investigates the influence of different flow-gas compositions on both the off-gas and the black mass achieved, as well as the effects on the ESLR process.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of O 2 to the process suggests increased CO 2 formation in the exhaust gas due to combustion reactions as well. Accordingly, in this study it is to be evaluated whether the oxidation behavior of the NMC oxides, or the favored formation of Li 2 CO 3 under CO 2 atmospheres expected from the literature [33,34], prevails as a function of the O 2 addition. To assess carbonate formation in the context of the thermal pre-treatment of battery materials, this study is the first, to the authors' knowledge, to determine the inorganic carbon content after water leaching.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Numerous studies show approaches for recycling of Li-ion batteries including sulfur-containing materials as well. [12][13][14] The preparation of Li-rich (Li 2 Fe)SO using non-toxic and low-cost raw materials such as lithium oxide, sulfur, and iron in a onestep solid-state reaction (SSR) has been reported. 4,5 This process is characterized by its simplicity and the absence of hazardous chemicals or solvents.…”
Section: Introductionmentioning
confidence: 99%